2020
DOI: 10.1038/s41598-020-73692-y
|View full text |Cite
|
Sign up to set email alerts
|

Learning curve analysis of applying Seprafilm hyaluronic acid/carboxymethylcellulose membrane during laparoscopic hysterectomy

Abstract: This study was designed to evaluate the learning curve of applying Seprafilm (modified hyaluronic acid and carboxymethylcellulose; Genzyme, Cambridge, MA, USA) during laparoscopic hysterectomy or subtotal hysterectomy with or without adnexectomy. In this retrospective cohort study, 35 patients who underwent laparoscopic hysterectomy or subtotal hysterectomy with or without adnexectomy were enrolled. The Seprafilm was cut into 4 pieces, rolled up with a trimmed plastic sleeve and delivered through an incision w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…Additionally, it is much easier to pull out the gauze than the backing paper of Seprafilm through a trocar. Through our method, the average time to complete a placement for one sheet of Seprafilm is approximately 100 seconds, which is acceptable as stated in other reports 4,5,7 . The important technical knack of this method is to remove remaining fluid in the abdominal cavity and at intra‐trocar sites before applying Seprafilm.…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations
“…Additionally, it is much easier to pull out the gauze than the backing paper of Seprafilm through a trocar. Through our method, the average time to complete a placement for one sheet of Seprafilm is approximately 100 seconds, which is acceptable as stated in other reports 4,5,7 . The important technical knack of this method is to remove remaining fluid in the abdominal cavity and at intra‐trocar sites before applying Seprafilm.…”
Section: Discussionsupporting
confidence: 51%
“…However, the fragile and sticky characteristics of Seprafilm cause many surgeons to hesitate from using it for deep surgical sites, such as the pelvic wall and retroperitoneal surface, with laparoscopic techniques. There have been several studies that introduced different methods for the placement of Seprafilm during laparoscopic surgery, such as grasping and rolling it directly with forceps, [3][4][5] wrapping it with its backing paper, 6,7 and using an introducer. [8][9][10][11] Although those methods are well-designed and performed placement of Seprafilm with high success rates, some weak points remain.…”
Section: Materials and Surgical Techniquementioning
confidence: 99%
See 1 more Smart Citation
“…GM142 showed fewer abnormal changes in bleeding-related laboratory test results compared with Seprafilm, and certain physiological benefits of the gelatin film as an adhesion barrier were suggested. Because trocars were not used in that GM142 study and recent reports 16,17 demonstrated the laparoscopic application of Seprafilm, a study directly comparing laparoscopic application of GM142 and Seprafilm would be interesting.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the results contradict the findings of Heathcote et al [ 11 ] who were modeling and observing human cognitive performance and found out that the exponential law is the best to describe an individual learner and that the power law may be observed only at the generalization level. However, the power law was again better at describing a combined motor-cognitive task [ 40 ]. There is additional research needed to explain why and when human and machine learners might be different in their performances.…”
Section: Discussionmentioning
confidence: 99%